Behavior of the acawa coffee variety with the application of soil fertilizers in nursery - García Cabrera, Juan (2024)
The research on the behavior of the Arabica coffee variety (Coffea arabica) Var. Acawa with the application of soil fertilizers during the nursery stage aimed to analyze the behavior of the Arabica coffee cultivar Var. Acawa and to identify the best soil fertilizer that enhances the morphological development of coffee seedlings. An experimental design of randomized complete blocks with four repetitions was applied in the methodology. The evaluated variables were plant height, number of leaves per plant, leaf length and width, petiole length, and root length. The results indicate that the greatest plant height was observed in the Yaramila Complex and Yara Rafos treatments, surpassing the control by 14.41% and 11.96%, respectively. Although no statistical differences were found, the greatest leaf length was recorded in Yara Rafos with 6.75 cm; the largest leaf diameter was observed where Yaramila Complex (9.50 cm) and Yara Rafos (9.30 cm) were applied; the longest petiole length was recorded in Yaramila Complex (10.48 cm) and Yara Rafos (10.83 cm), and the greatest root length, with no statistical difference, was seen in Yara Rafos at 14.98 cm, surpassing the control by 7.67%. The fertilizer that had the most impact on the morphological development of Acawa coffee seedlings was Yaramila Complex, followed by Yara Rafos, outperforming the control in all evaluated characteristics. It is concluded that the best fertilizer alternatives for Acawa coffee nurseries are Yaramila Complex and Yara Rafos.